2015 songwriter's market - Duncan, James (Editor); Writer's Digest Books (Firm) (Cincinnati, Ohio : Writer's Digest Books, 2014)
Includes access to the webinar "Song Seeds: how to jump-start your songwriting process" from author and Berklee College of Music professor Mark Simos.
Getting started. How to use Songwriter's Market ; Where should I send my songs? ; Demo recordings ; How do I submit my demo? ; How do I avoid the rip-offs? ; Submission strategies -- Music biz basics. Royalties ; Copyright ; Career songwriting ; Contracts -- Articles & interviews. Make the most of the digital age / Allison Malafronte ; Get the most from music conferences / Graydon James ; Doing it all: Scott Mathews / James Duncan ; Cross-country collaboration / Jennifer Billock ; Music licensing for songwriters / Michael St. James ; Become a DIY producer / Mark Bacino ; The business of creativity / James Duncan ; So, you're moving to Nashville? / Scarlet Keys -- Managing your work. Songwriting calendar -- Markets. Music publishers ; Record companies ; Record producers ; Managers & booking agents ; Music firms ; Play producers & publishers ; Classical performing arts ; Contests & awards -- Resources. Organizations ; Retreats & colonies ; Workshops & conferences ; Venues ; State & provincial grants ; Publications of interest ; Websites of interest ; Glossary -- Indexes. General index, ; Category indexes.
Includes bibliographical references and indexes.
Keywords: Music -- Writing and publishing -- Directories; Music -- Marketing -- Directories; Popular music -- Writing and publishing -- United States -- Directories; Popular music -- United States -- Marketing -- Directories; Music trade -- Directories